PENGARUH HOMOPHILY, PHYSICAL ATTRACTIVENESS, DAN CREDIBILITY TERHADAP PURCHASE INTENTION MELALUI PARASOCIAL INTERACTION PADA BEAUTY VLOGGER DI INDONESIA - Vita Alfaena, Widiya; Anggi Gumilang, Dendi (JURNAL LENTERA BISNIS, 2026)
The rapid growth of the cosmetic industry in Indonesia has been accompanied by an increasing reliance of young consumers on social media to seek product recommendations. Indonesian beauty vloggers such as Tasya Farasya, Nanda Arsyinta, Jharna Bhagwani, Rachel Goddard, and Abel Cantika have become relevant subjects for this study. This research aims to analyze the influence of Homophily, Physical Attractiveness, and Credibility on Purchase Intention through Parasocial Interaction among beauty vloggers in Indonesia. This study employed a quantitative approach, with data collected through Google Forms distributed to female consumers who actively follow beauty vloggers. A total of 237 respondents participated in this research. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The results indicate that homophily and credibility positively influence parasocial interaction. Furthermore, parasocial interaction, homophily, physical attractiveness, and credibility positively influence purchase intention. Parasocial interaction was also found to mediate the relationship between homophily and credibility on purchase intention. However, physical attractiveness does not influence parasocial interaction, and parasocial interaction does not mediate the relationship between physical attractiveness and purchase intention. Therefore, hypotheses H1, H3, H4, H5, H7, and H10 are supported, while hypotheses H2, H6, and H9 are rejected.